Youth Unemployment : A comparison between Italy and the Czech Republic - Roselli, Eileen; Mazouch, Petr, 1981-; Musil, Petr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Youth unemployment presents an issue for governments in many countries around the world. Italy is among those with the highest unemployment rates in the European Union. On the other hand, the Czech Republic has managed to achieve the lowest unemployment rate in the EU. The goal of this thesis will be to explore the main differences between the labour markets in Italy and the Czech Republic. Furthermore, this thesis will investigate the reasons for which Italians seem to face more obstacles than Czechs when first entering the labour market, despite both countries having well developed and funded education systems. Additionally, this thesis will explore other societal factors affecting the situation of young people entering the labour market in Italy compared to those in the Czech Republic.
Vedoucí práce: Petr Mazouch
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses